‘That’s kind of under my work blanket’—redeployment experiences of children’s hospital staff during the covid-19 pandemic: a qualitative interview study - Paula Kelly; Susie Aldiss; Jo Wray; Cecilia Vindrola-Padros; Faith Gibson (BMC Health Services Research)
Abstract Background During COVID-19 pandemic, a rapid readjustment to continued delivery of healthcare was required. Redeployment is an intentional process to mobilise human resources by reassigning a healthcare worker to a new role or new work location, to achieve sustainable delivery of patient care. We report redeployment experiences of staff from a specialist children’s hospital during first and second waves of the United Kingdom COVID-19 pandemic. Methods This study focuses on a specialist children’s hospital where redeployment occurred externally to adult intensive care units and other COVID-19 specific initiatives, and internally as some service activity reduced and others expanded. This was a study of staff experiences using a qualitative rapid appraisal design. Hospital staff participated in an in-depth one-to-one telephone interview. We used a semi-structured interview guide, and recorded and transcribed all interviews. Rapid Research Evaluation and Appraisal Lab sheets were used to share data; team-based analysis was facilitated using a framework approach. Results Recruitment and interviews took place from March-November 2021. Twenty-four staff participated: 17 nurses, five doctors and two other healthcare professionals. Interviewees articulated their experiences of redeployment both within the specialist children’s hospital and externally to other health settings (predominantly adult intensive care). Redeployment impacted staff in multiple ways professionally and personally and was reported to be both challenging and rewarding. The reality of working in different settings was felt by everyone, with unfamiliar environments, patient safety, and delivery of a more task-based model of care creating some negative experiences. We identified five main themes: (i) Drivers and Agency; (ii) Journey to Redeployment; (iii) Working Reality; (iv) Personal Impact and Support; (v) Professional Disruption. Conclusions Although experience of those redeployed varied, prior background of working in intensive care settings and with adult patients, with opportunities to share practice with colleagues, mitigated challanges for our participants. Positive experiences were associated with perceptions of support received, being welcomed in the new setting, and feeling valued. This study also highlights the act of ‘volunteering’, the nature of ‘voluntariness’ and the difference that may exert on the overall redeployment experience. Future guidance would be encouraged to consider the voluntary nature of redployment.